The general equation of a circle with center (a , b) and radius r is given by ( x - a)^2 + (y - b)^2 = r^2

Substituting the values given:

(x - 2)^2 + (y + 3)^2 = 25

=> x^2 + 4 - 4x + y^2 + 9...

## Get

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The general equation of a circle with center (a , b) and radius r is given by ( x - a)^2 + (y - b)^2 = r^2

Substituting the values given:

(x - 2)^2 + (y + 3)^2 = 25

=> x^2 + 4 - 4x + y^2 + 9 + 6y = 25

=> x^2 + y^2 - 4x + 6y - 12 = 0

**The required equation of the circle is x^2 + y^2 - 4x + 6y - 12 = 0**